Identifying a Reliable Boredom Induction. Issue 1 (August 2014) - Markey, Amanda; Chin, Alycia; Vanepps, Eric M.; Loewenstein, George
None of the tasks used to induce boredom have undergone rigorous psychometric validation, which creates potential problems for operational equivalence, comparisons across studies, statistical power, and confounding results. This methodological concern was addressed by testing and comparing the effectiveness of six 5-min. computerized boredom inductions (peg turning, audio, video, signature matching, one-back, and an air traffic control task). The tasks were evaluated using standard criteria for emotion inductions: intensity and discreteness. Intensity, the amount of boredom elicited, was measured using a subset of the Multidimensional State Boredom Scale. Discreteness, the extent to which the task elicited boredom and did not elicit other emotions, was measured using a modification of the Differential Emotion Scale. In both a laboratory setting (Study 1; N = 241) and an online setting with Amazon Mechanical Turk workers (Study 2; N = 416), participants were randomly assigned to one of seven tasks (six boredom tasks or a comparison task, a clip from Planet Earth ) before rating their boredom using the MSBS and other emotions using the modified DES. In both studies, each task had significantly higher intensity and discreteness than the comparison task, with moderate to large effect sizes. The peg-turning task outperformed the other tasks in both intensity and discreteness, making it the recommended induction. Identification of reliable and valid boredom inductions and systematic comparison of their relative results should help advance state boredom research.